Binding Assay of Cytosolic Proteins to the Cytoskeleton - Stefano Del Duca; Giampiero Cai (Bio-Protocol, 2013)
Many cellular proteins interact with the cytoskeleton (both actin filaments and microtubules), either dynamically or permanently. This interaction is required during different aspects of the cell life, for example during the process of cell division. In addition, many enzymes interact transiently with actin filaments and microtubules in order to promote their cellular distribution. Several substances with inhibitory capacity can affect this binding and cause damages to cells. This protocol allows to analyze whether a protein interacts with either actin filaments or microtubules and, when applicable, the conditions controlling this interaction.The test is based on the specific binding between the protein of interest and the cytoskeletal filaments. As shown schematically in the diagram of example (see below), the test starts from the cell lysate to which actin filaments (produced from monomeric actin) are added. The mixture (performed under different experimental conditions chosen by the operator) is then incubated so that the protein of interest (in the example, myosin) binds to actin filaments. The sample is then centrifuged in order to separate unbound or weakly-bound proteins from actin filaments to which both the protein of interest and, eventually, traces of less specific proteins are associated.